Role of Wet Mount and Cytospin Smears in Diagnosing Urothelial Carcinoma: A Descriptive Observational Study - Asha Patil; P Shashikala; Pratima M Pattar; K Arpitha (National Journal of Laboratory Medicine, 2022)
Introduction: Most common carcinomas of lower urinary tract are of urothelial type in which, majority of them occur in the bladder. The demonstration of exfoliated neoplastic cells in urine sediment cytology is one of the choices of investigation. Aim: To study the morphology of atypical cells of urine sediment in unstained wet mount preparation and urine sediment obtained by cytospin smear stained with Papanicolaou stain. Materials and Methods: It was a descriptive observational study done over a period of 29 months i.e., from July 2016 to December 2018 at SS Institute of Medical Sciences and Research Centre, Davangere, Karnataka, India. Using non probability sampling method, 50 urine samples were analysed by DIRUI-H 500 a semi automatic urine analyser, which were further examined by wet mount preparation and cytospin smear stained with papanicolaou stain. Results were analysed by whether the smears were positive or negative for atypical cells based on the cytological and nuclear details. Results: The yield of Red Blood Corpuscles (RBCs) was significantly increased in cytospin preparation with morphology of RBCs was better appreciated in wet mount compared to cytospin preparation. The yield of atypical cells was significantly increased in cytospin preparation with the morphology of atypical cells were better appreciated in pap stained cytospin preparation compared to wet mount urine examination. Conclusion: Overall, cell yield and preservation of White Blood Corpuscles (WBCs), epithelial cell and atypical cells morphology was better in cytospin preparation, while RBCs were better appreciated in wet mount preparation. Cytospin technology is a quick, efficient and cost effective method for increasing cell yield in less cellular samples and also helps in providing better cellular morphological details.